Graphical aids for visualising the space-time coordinates of events created by light signals emitted by moving sources. (13th February 2006) - Paunescu, Doru; Rothenstein, Bernhard
Relativistic space-time diagrams are presented, displaying in true values the space-time coordinates of events created by light signals emitted by moving sources, as detected from inertial reference frames in relative motion. The diagrams are used in order to solve the problem of the rays and mirrors in the Michelson-Morley experiment.